ChemInform Abstract: Nucleophile‐Dependent Regioselective Reaction of (S)‐4‐Benzyl‐2‐fluoroalkyl‐1, 3‐oxazolines. Issue 35 (8th August 2013) - Jiang, Haizhen; et al., et al.
Abstract Substituted oxazolines, oxazolidines, or fluorinated acetamides are obtained depending on the nucleophile used.